2003
DOI: 10.2308/acch.2003.17.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Firm Value and Employee Attitudes on Workplace Quality

Abstract: This paper investigates the relation between the value of a firm and employee attitudes on the firm's workplace quality—workplace attitudes. Workplace attitude refers to recognition of those organizational characteristics that enhance employee work experiences and assist employees in balancing their jobs and personal lives. Using inclusion on Fortune's annual list of “The 100 Best Companies to Work for in America” as a proxy for successful efforts in creating high workplace attitudes, we compare the market val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 10 publications
4
57
0
1
Order By: Relevance
“…According to (Ballou et al, 2003;Fulmer et al, 2003) Fortune's 100 best companies have higher market value and better return that matched firm not on the list. Companies ranked in top one third of the list have higher market value than bottom one third of the list (Ballou et al, 2003).…”
Section: Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…According to (Ballou et al, 2003;Fulmer et al, 2003) Fortune's 100 best companies have higher market value and better return that matched firm not on the list. Companies ranked in top one third of the list have higher market value than bottom one third of the list (Ballou et al, 2003).…”
Section: Firm Performancementioning
confidence: 99%
“…Companies ranked in top one third of the list have higher market value than bottom one third of the list (Ballou et al, 2003). Fulmer et al (2003) has shown that positive employee relation do lead to better performance (as measured by both accounting and market data: ROA and market-to-book value ratios).Thus being in a list of best employer is a strong marketing or employer branding toll which leads to better attraction and retention in long run (Joyce,2001).…”
Section: Firm Performancementioning
confidence: 99%
“…POS has been determined to strengthen affective commitment and increased performance (Eisenberger et al, 2001;Rhoades & Eisenberger, 2002). There is also increasing evidence that the "best" places to work improve organizational performance (Arthur, 2003;Ballou, Godwin, & Shortridge, 2003;Boyle, 2006;Fulmer, Gerhant, & Scott, 2003;B. May, Lau, & Johnson, 1999).…”
Section: Management Theory and Caringmentioning
confidence: 99%
“…Companies included on Fortune's 100 best companies list have higher market values and better return than matched firm not included on the list (Ballou et al, 2003;Fulmer et al, 2003). The market values of firm ranked in top one third of the list were higher than firms ranked in the bottom one third of the list (Ballou et al, 2003).…”
Section: F) Firm Performancementioning
confidence: 91%
“…The market values of firm ranked in top one third of the list were higher than firms ranked in the bottom one third of the list (Ballou et al, 2003). Fulmer et al, (2003) showed that positive employee relation are beneficial for companies and may be related to improved performance (as measured by both accounting and market data: ROA and market-to-book value ratios).…”
Section: F) Firm Performancementioning
confidence: 97%